Identification of Peroxiredoxin-5 in Bovine Cauda Epididymal Sperm - Nagdas, Subir K (2013)
Developing spermatozoa require a series of post-testicular modifications within the luminal environment of the epididymis to achieve maturation; this involves several surface modifications including changes in plasma membrane lipids, proteins, carbohydrates, and alterations in the outer acrosomal membrane. Epididymal maturation can therefore allow sperm to gain forward motility and fertilization capabilities. The objective of this study was to identify maturation dependent protein(s) and to investigate their role with the production of functionally competent spermatozoa. Lectin blot analyses of caput and cauda sperm plasma membrane fractions identified a 17.5kDa Wheat Germ Agglutinin (WGA) binding polypeptide present in the cauda sperm plasma membrane not in the caput sperm plasma membrane. Among the several WGA stained bands, the presence of a 17.5kDa WGA binding polypeptide band was detected only in cauda epididymal fluid not in caput epididymal fluid suggesting that the 17.5kDa WGA-binding polypeptide is secreted from the cauda epididymis and binds to the cauda sperm plasma membrane during epididymal transit. Proteomic identification of the 17.5kDa polypeptide yielded 13 peptides that matched the sequence of peroxiredoxin-5 (PRDX5) protein (Bos Taurus). We propose that bovine cauda sperm PRDX5 acts as an antioxidant enzyme in the epididymal environment, which is crucial in protecting the viable sperm population against the damage caused by endogeneous or exogeneous peroxide.